2015
DOI: 10.1128/jb.02288-14
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Functional Characterization of WxL Proteins from Enterococcus faecium Reveal Surface Proteins Involved in Extracellular Matrix Interactions

Abstract: fThe WxL domain recently has been identified as a novel cell wall binding domain found in numerous predicted proteins within multiple Gram-positive bacterial species. However, little is known about the function of proteins containing this novel domain. Here, we identify and characterize 6 Enterococcus faecium proteins containing the WxL domain which, by reverse transcription-PCR (RT-PCR) and genomic analyses, are located in three similarly organized operons, deemed WxL loci A, B, and C. Western blotting, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
(79 reference statements)
1
39
0
Order By: Relevance
“…In addition, WxL proteins from locus A were able to bind collagen and fibronectin and deletion of all 3 loci-attenuated virulence in a mixed infection rat endocarditis model. 43 Glycolipids and polysaccharides are also important components of the enterococcal cell envelope. Lipoteichoic acid is an antigenic component of gram-positive cell walls, and antibodies directed against this epitope were shown to enhance opsonization and killing of enterococci by complement and leukocytes.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…In addition, WxL proteins from locus A were able to bind collagen and fibronectin and deletion of all 3 loci-attenuated virulence in a mixed infection rat endocarditis model. 43 Glycolipids and polysaccharides are also important components of the enterococcal cell envelope. Lipoteichoic acid is an antigenic component of gram-positive cell walls, and antibodies directed against this epitope were shown to enhance opsonization and killing of enterococci by complement and leukocytes.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…2a and Table 2B. Of particular significance is the protein gi|515938667 containing a WxL domain, which is characteristic of proteins that are non-covalently anchored to peptidoglycan of the cell wall (Galloway-Peña et al 2015) and play a role in carbon source acquisition or adhesion to the host cells (Siezen et al 2006). Also, the protein gi|518123066 seems to be a lytic enzyme and is codified by a gene (gene 25 of contig 19) previously identified among those upregulated at 18°C in comparison with 13 and 37°C (Table 1).…”
Section: Immunoproteome Analysis/immunoblot Analysis Of L Garvieae Pmentioning
confidence: 99%
“…Previous studies have shown that E. faecium cells express a variety of surface proteins that can contribute to adhesion (41). These include an endocarditis-and biofilm-associated pilus protein (Ebp fm ) (42), an enterococcal surface protein (Esp) (43), serine-glutamate repeat-containing protein A (SgrA) (44), and the WxL proteins (26). In addition, we identified a significant association between collagen adherence and the presence of a functional acm gene, encoding an adhesin of collagen, in clinical but not community isolates (45,46).…”
Section: Discussionmentioning
confidence: 76%
“…E. faecium genomic DNA was isolated from a single colony after overnight growth in BHI broth, as described previously (26). Plasmids were isolated from E. coli using Wizard Plus SV MiniPreps system columns (Promega Corporation).…”
Section: Methodsmentioning
confidence: 99%